2016
DOI: 10.1113/jp271681
|View full text |Cite
|
Sign up to set email alerts
|

The L‐type Ca2+ channel facilitates abnormal metabolic activity in the cTnI‐G203S mouse model of hypertrophic cardiomyopathy

Abstract: Key pointsr Genetic mutations in cardiac troponin I (cTnI) are associated with development of hypertrophic cardiomyopathy characterized by myocyte remodelling, disorganization of cytoskeletal proteins and altered energy metabolism.r The L-type Ca 2+ channel is the main route for calcium influx and is crucial to cardiac excitation and contraction. The channel also regulates mitochondrial function in the heart by a functional communication between the channel and mitochondria via the cytoskeletal network.r We fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

12
49
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 56 publications
12
49
0
Order By: Relevance
“…5 Cardiac myocytes isolated from mice with disease causing cardiac troponin I mutation Gly203Ser (cTnI-G203S), exhibited altered I Ca-L kinetics, and a significantly greater increase in C m and mitochondrial oxygen consumption (measured as an increase in flavoprotein oxidation and formation of formazan from tetrazolium salt) in response to activation of the channel. 6 Consistent with our original hypothesis, the alterations in C m were not due to alterations in intracellular calcium, because the responses occurred under calcium-free conditions. Further to this, diastolic intracellular calcium levels were similar in cTnI-G203S versus wt mice under basal conditions, and in response to activation of I Ca-L .…”
supporting
confidence: 86%
See 4 more Smart Citations
“…5 Cardiac myocytes isolated from mice with disease causing cardiac troponin I mutation Gly203Ser (cTnI-G203S), exhibited altered I Ca-L kinetics, and a significantly greater increase in C m and mitochondrial oxygen consumption (measured as an increase in flavoprotein oxidation and formation of formazan from tetrazolium salt) in response to activation of the channel. 6 Consistent with our original hypothesis, the alterations in C m were not due to alterations in intracellular calcium, because the responses occurred under calcium-free conditions. Further to this, diastolic intracellular calcium levels were similar in cTnI-G203S versus wt mice under basal conditions, and in response to activation of I Ca-L .…”
supporting
confidence: 86%
“…Further to this, diastolic intracellular calcium levels were similar in cTnI-G203S versus wt mice under basal conditions, and in response to activation of I Ca-L . 6 We demonstrated that the response involved F-actin and b-tubulin and that the hyperpolarisation of the C m occurred due to increased block of mitochondrial VDAC by b-tubulin. 6,7 This finding is supported by studies demonstrating that b-tubulin associates with and regulates the open/closed state of mitochondrial VDAC.…”
mentioning
confidence: 77%
See 3 more Smart Citations